2018
DOI: 10.1177/0892020618783817
|View full text |Cite
|
Sign up to set email alerts
|

Human resource policy and teacher appraisal in Ontario in the era of professional accountability

Abstract: This article suggests that the implementation of human resource policies such as teacher performance appraisal (TPA) is a disturbance to the school organizational climate. Based on my cross-examination of both school managers’ and teachers’ discourse, I suggest that a new leadership approach needs to be developed at the school level to effectively coordinate TPA implementation in such a way that it can enhance teacher professional growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…Table 3 illustrates that: teachers participate in classroom observation (mean=4.03); classroom observation enables the appraiser to observe all aspects of a teacher's teaching (mean=4.41). This finding agrees with earlier findings by Dandala (2019), which revealed that the most frequently utilized appraisal process remains observation based given it provides the only setting in which all the aspects of teaching can be observed. Moreover, findings revealed that classroom observation enables teachers identify their aspects of teaching that need improvement (mean=3.88); classroom observation provides immediate feedback to teachers about their teaching (mean=4.69).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Table 3 illustrates that: teachers participate in classroom observation (mean=4.03); classroom observation enables the appraiser to observe all aspects of a teacher's teaching (mean=4.41). This finding agrees with earlier findings by Dandala (2019), which revealed that the most frequently utilized appraisal process remains observation based given it provides the only setting in which all the aspects of teaching can be observed. Moreover, findings revealed that classroom observation enables teachers identify their aspects of teaching that need improvement (mean=3.88); classroom observation provides immediate feedback to teachers about their teaching (mean=4.69).…”
Section: Resultssupporting
confidence: 93%
“…The most frequently utilized appraisal process remains observation based, which is widely regarded as the best, given it provides the only setting in which all aspects of teaching can be observed (Dandala (2019). Zang & Ng (2017) assert that it is through classroom observation that the evaluator can best take on an understanding of a teacher's effectiveness, as it allows physical classroom environment, students' engagement and a teacher's standards of conduct to be considered.…”
Section: Performance Appraisalmentioning
confidence: 99%
“…Deming (1986) and Breedlove (2011) further state that if not used properly, teacher appraisals can lead to frustration, anger and reduced levels of motivation. Dandala (2019: 8) suggests that ‘the lack of enthusiasm among teaching employees can be interpreted as a token of distrust in the [teacher performance appraisal] process’. Research has indicated that the methods of appraisal are often flawed (Jacob and Lefgren, 2007).…”
Section: Introductionmentioning
confidence: 99%